PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA PEGAWAI PADA BANK MANDIRI CABANG SOROWAKO - Adela Ayu Badiaturahmi; Uhud Darmawan Natsir; Nurul Fadilah Aswar (Bajang Institute, 2025)
This research aims to determine the effect of rewards and punishments on employee work motivation at Bank Mandiri Sorowako Branch. This research is quantitative research. The population in this study was 40 employees of Bank Mandiri Sorowako Branch. Determination of the sample using a saturated sampling technique using all members of the population as samples, namely 40 people. The data collection technique used was a questionnaire. The data analysis technique used is quantitative analysis in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression tests, partial tests, simultaneous tests, and determinant coefficient tests using the SPSS application. Research result. This shows that the award (X1) partially has a positive and significant effect on work motivation at Bank Mandiri Sorowako Branch. And punishment (X2) partially has a positive and significant effect on employee work motivation at Bank Mandiri Sorowako Branch. And rewards (X1) and punishments (X2) simultaneously have a positive and significant effect on employee work motivation at Bank Mandiri Branch, Sorowako.